Dried Vegetables as Potential Clean-Label Phosphate Substitutes in Cooked Sausage Meat - Weigel, Ingrid; Nistler, Sarah; Pichner, Rohtraud; Budday, Silvia; Gensberger-Reigl, Sabrina (Foods, 2023)
While phosphates are key additives in sausage production, their use conflicts with consumer preferences for “natural” foods. In this study, we investigated the potential of using vegetables as “clean-label” phosphate substitutes and their effects on water holding capacity, consumer acceptance, color, softness, and tenderness. Six freeze-dried vegetables with a pH above 6.0 were added to sausage meat on a laboratory scale. Adding 1.6% freeze-dried Brussels sprouts or Red Kuri squash resulted in a similar weight gain (7.0%) as the positive control of 0.6% commercial phosphate additive. Higher vegetable concentrations (2.2–4.0%) caused a significant increase in weight (p ≤ 0.05, 10.4–18.4% weight gain). Similar stress was needed to compress sausages containing 1.6/4.0% Brussels sprouts (14.2/11.2 kPa) and the positive control (13.2 kPa). Indentation tests also led to similar softness results for the sausages prepared with 1.6/4.0% Brussels sprouts (15.5 kPa/16.6 kPa) and the positive control (16.5 kPa). A force of 1.25 N was needed to shear the positive control, while 1.60 N/1.30 N was needed for the samples (1.6/4% Brussels sprouts). In summary, the present study indicates that freeze-dried vegetables have the potential to effectively replace phosphate in meat products.
CRIS-Team Scopus Importer:2023-06-09
Keywords: clean-label; freeze-dried vegetables; meat products; phosphate; phosphate substitutes; sausages

Spatiotemporal modeling of first and second wave outbreak dynamics of COVID‐19 in Germany - Lippold, Dorothee; Kergaßner, Andreas; Burkhardt, Christian; Kergaßner, Matthias; Loos, Jonas; Nistler, Sarah; Steinmann, Paul; Budday, Dominik; Budday, Silvia (Biomechanics and Modeling in Mechanobiology, 2021)
The COVID-19 pandemic has kept the world in suspense for the past year. In most federal countries such as Germany, locally varying conditions demand for state- or county-level decisions to adapt to the disease dynamics. However, this requires a deep understanding of the mesoscale outbreak dynamics between microscale agent models and macroscale global models. Here, we use a reparameterized SIQRD network model that accounts for local political decisions to predict the spatiotemporal evolution of the pandemic in Germany at county resolution. Our optimized model reproduces state-wise cumulative infec- tions and deaths as reported by the Robert Koch Institute and predicts the development for individual counties at convincing accuracy during both waves in spring and fall of 2020. We demonstrate the dominating effect of local infection seeds and identify effective measures to attenuate the rapid spread. Our model has great potential to support decision makers on a state and community politics level to individually strategize their best way forward during the months to come.
Keywords: COVID-19 · SIQRD model · Mesoscale outbreak dynamics · Germany